Indications, design considerations, and clinical outcomes of implant-supported fixed prostheses - Alfaer, Ali Salem; Bakhsh, Khulood Khalid; Alyami, Ibrahim Mohammed; Fallatah, Rawaa Mohammed; Saloum, Mashael Saleh; AlHarbi, Nouf Yahya; Al Otaibi, Suha Dhaifallah; Alotaibi, Bandar Zaid; AL Meheini, Salem Abdullah; AL Shalawi, Sahar Safar; Bushnaq, Abdulrahman Mohammed (International Journal Of Community Medicine And Public Health, 2023)
Implant-supported fixed prostheses are a highly successful treatment option for replacing missing teeth, offering improved esthetics, function, and patient satisfaction. Design considerations play a crucial role in achieving optimal outcomes. Implant distribution and angulation should be carefully planned to ensure balanced load distribution and biomechanical stability. Occlusal considerations are vital to minimize mechanical complications and implant overloading, with proper adjustments and occlusal schemes implemented. The emergence profile should replicate natural tooth contours for esthetic integration and ease of oral hygiene maintenance. Material selection is essential, considering factors such as occlusal loading, esthetic requirements, and patient-specific considerations. Biomechanical analysis helps identify stress distribution patterns and optimize prosthesis design for long-term success. Patient satisfaction is high, with improved chewing ability, speech, and overall quality of life reported. Long-term success rates exceed 90%, influenced by implant survival, peri-implant health, maintenance of prosthesis integrity, and patient satisfaction. Thorough patient assessment, treatment planning, precise surgical and prosthetic execution, and comprehensive follow-up care are crucial for favorable outcomes. Implant-supported fixed prostheses provide functional and esthetic restorations, enhancing oral health and overall well-being.